The Recovery of Vegetal Waste in the form of Home-Composting - Anca ȘERBAN; Adrian LEOPA (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
Composting the vegetable waste is an ecological alternative to their treatment by incineration or storage on landfills. The recovery of vegetable waste for obtaining compost is a beneficial method both by keeping a clean environment and enriching the soil. The vegetable waste decomposes and leave its intake nutrient in the soil for plants and other crops growth. The paper includes the chemical analysis and testing results of the compost obtained with garden vegetable waste (dried leaves, branches, bark, stems, flowers and herbs).